87P Clinical outcomes of metastasic melanoma patients treated with ipilimumab and nivolumab: A single institution experience. (15th December 2019) - Oberoi, H K Oberoi; Vila, C M; Rodriguez, A; Coronel, D Pesantez; Moreno, F Aya; Puig, M C Font; Fernandez, A M Arance
Abstract: Background: Immune checkpoint combination therapy with nivolumab and Ipilimumab for untreated metastatic melanoma has shown higher rates of response rates, progression free survival and overall survival compared to monotherapy (Long et al. ESMO 2019), including patients with brain metàstasis, at a cost of higher toxicity. Several clinical factors had been identified as prognostic of response to immunotherapy, such as LDH, dLNR and toxicity. Methods: We analysed all patients with melanoma treated with ipilimumab and nivolumab between March 2017 and September 2019 institution. Statistical analysis was preformed with IBM SPSS Statistics 24.0. Results: 42 patients (p) treated with ipilimumab and nivolumab were included. 22 (52.4%) men, 38 (90%) ECOG 0-1 (%). Stages at treatment: IVA (n = 4), IVB (n = 11), IVC (n = 17), IVD (n = 9). 20p (48%) presented a positive BRAF mutation. 10p (24%) had a previous adjuvant treatment. LDH: N (n = 25, 60%), <1.2xULN (n = 7, 16%), >1.2xULN (n = 10, 24%). Cycles completed: 1 (n = 4), 2 (n = 16), 3 (n = 7), 4 (n = 12). Best Overall Response (BOR): Progressive disease (n = 22, 52%), stable disease (n = 4, 10%), partial response (n = 10, 24%), complete response (n = 6, 14%). Immunorelated adverse events (irAEs): Yes (n = 27, 64, 3%), no (n = 15, 35, 7%). Hepatitis 15, colitis 5, hypophysitis 5, thyroiditis 1, Nephritis 1. Grades: 1 (n = 2), 2 (n = 14), 3 (n = 8), 4 (n = 3), Number of CNS lesions: 1 (n = 0), 2 (n = 2), 3 (n = 0) and >3 (n = 8). 9 patients presented CNS disease, 4 of them had symptoms requiring steroid treatment. OS from the whole population was 34.7 months (m) (22.6-46.8, IC 95%). Independent predictors of OS where ECOG (p = 0.1, IC 95%), no previous treatment (p = 0.07, IC 95%), LDH (p = 0.02, IC 95%), irAES (p = 0.05), No 25.6m (8, 9-42, 4), Yes 39.1m (26.1-52.2), IC 95%). BRAF status, cycles, number of extracranial lesions, number of intracranial lesions and dNLR were not found to be predictors of OS. A significant association was found between BOR and irAEs (p = 0.009), LDH (p = 0.018), ECOG (p = 0.027). Conclusion: In our cohort, LDH, ECOG and irAEs and no previous treatment were found predictors of response and overall survival. Our median OS and ORR were slighly slower than reported in trials. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: A.M. Arance Fernandez: Honoraria (self): Bristol-Myers Squibb. All other authors have declared no conflicts of interest.